Aerodynamic Drag Reduction Around Vehicles Using a Curved Deflector - Maine, Mohamed; El Oumami, Mohamed; Bouksour, Otmane (International Journal of Integrated Engineering, 2023)
A passive flow control on a generic car model was numerically studied. The Ahmed model with rear slant angle of 25° was used to study the aerodynamic effects. The concave deflector was tested for the first time in this paper to minimize the drag coefficient. The deflector was fixed between the end of the roof and the top of the rear window. Simulations were firstly performed for different straight deflector’s length rates based on the length of the model, for Reynolds number Re=7.89×105. A significant drag reduction was observed for the high length rate studied. Secondly, the length rate was fixed, and the deflector was investigated for different curvature radius and inclination angles. It was concluded that the Ahmed model with concave deflector gives the best drag reduction, compared to the model with straight deflector and the model without deflector. It was observed that the installation of a concave deflector on the Ahmed model widen the wake zone and remove the vortices from the rear base. For this case, the lift coefficient was reduced, this improves the stability of vehicle on the road at high speed.